Randomised controlled trial to compare the effect of PIOMI (structured) and routine oromotor (unstructured) stimulation in improving readiness for oral feeding in preterm neonates - Singh, Pari; Malshe, Nandini; Kallimath, Aditya; Garegrat, Reema; Verma, Arjun; Nagar, Nandini; Maheshwari, Rajesh; Suryawanshi, Pradeep (Frontiers in Pediatrics, 2023)
Background: Oral motor stimulation interventions improve oral feeding readiness and earlier full oral feeding in preterm neonates. However, using a structured method may improve the transition time to full oral feeds as well as feeding efficiency with respect to weight gain and exclusive breastfeeding as compared to an unstructured intervention. Objective: To compare the effect of Premature Infant Oral Motor Intervention (PIOMI) and routine oro-motor stimulation (OMS) on oral feeding readiness Methods: Randomised controlled trial conducted in a neonatal intensive care unit between June-December 2022. Preterm neonates, 29 +0 -33 +6 weeks corrected gestational age were studied. Intervention arm received PIOMI and comparator arm received OMS. Primary outcome: time to oral feeding readiness by Premature Oral Feeding Readiness Assessment Scale (POFRAS) score ≥30. Secondary outcomes: time to full oral feeds, duration of hospitalisation, weight gain and exclusive breastfeeding rates. Results: Total 84 neonates were included, randomised 42 each into PIOMI and OMS. The mean chronological age and time to oral feeding readiness was lower by 4.6 and 2.7 days respectively, for PIOMI. The transition time to full oral feeds was 2 days lower for PIOMI and the duration of hospitalisation was 8 days lower. The average weight gain was 4.9 g/kg/day more and the exclusive breastfeeding rates at one month, and 3 months post discharge were higher by 24.5% and 27% for the PIOMI group. The subgroup analysis of study outcomes on the basis of gender and weight for gestational age showed significant weight gain on oral feeds in neonates receiving PIOMI. Similarly, the subgroup analysis on the basis of gestational age favoured the PIOMI group with significantly earlier transition time and weight gain on oral feeds for the neonates >28 weeks gestational age. The odds of achieving oral feeding readiness by 30 days ); full oral feeds by 45 days ); and exclusive breastfeeding at 1 month ) and 3 months (3.889 [1.186-12.749]) after discharge were higher with PIOMI. Conclusion: PIOMI is a more effective oromotor stimulation method for earlier and improved oral feeding in preterm neonates.